ANALYSIS OF WATER-SOLUBLE VITAMINS IN THE «AS RHEUM» FOOD ADDITIVE OBTAINED BASED ON THE COMBINATION OF ALLIUM ODORUM AND RHEUM (Scientific journal of the Fergana State University, 2024)
In this research work, based on the chemical composition of the above-ground parts of the leaves of the ruach plant growing in Namangan region and the above-ground parts of jusai plants growing in Fergana province in a ratio of 3:1 (consisting of 75% ruach and 25% jusai) obtained As Rheum food additive was studied by high-performance liquid chromatography method.